PENERAPAN PEMBELAJARAN SIMAYANG TIPE II PADA MATERI ASAM BASA - Siti Hasanah; Sunyono Sunyono; Tasviri Efkar (Universitas Lampung, 2015)
The pre-experimental research with One Group Pretest-Posttest Design was aimed to describe the practicality and effectiveness of SiMaYang Type II learning in growing mental models and concept mastery of students in acid base topic. The research was conducted at the 11th grade of IPA1, IPA2 and IPA3 SMA Gajah Mada Bandar Lampung as replication classes. The data analysis was done descriptively. The results showed that the implementation of SiMaYang Type II learning have high practicality and effectiveness in growing mental models and concept mastery of students in acid base topic. Mental models of three replication classes have the criteria of